OPTIMIZATION OF PUBLIC SECTOR HUMAN RESOURCES DEVELOPMENT IN IMPROVING THE QUALITY OF EDUCATION IN INDONESIA - Rochmansjah, Heru (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2024)
This article focuses on the importance of optimizing Human Resource (HRM) development in the public sector, in this case the Indonesian education sector, to improve the quality of education. Effective human resource management plays a vital role in achieving the goal of high-quality and sustainable education. This study explores various elements of HRM, including recruitment and selection, development and training, motivation and retention, performance evaluation, and well-being and work-life balance. Using qualitative research methods, data were collected through in-depth interviews, observations, and document studies from various educational institutions in Indonesia. The research findings suggest that optimizing HRM can contribute significantly to improving the quality of education. This article offers recommendations for HRM policies and practices that can be utilized by policymakers and practitioners in the Indonesian education sector.